THE ROLE OF ISLAMIC RELIGIOUS EDUCATION IN OVERCOMING ADOLESCENT CHARACTER CRISIS IN THE DIGITAL ERA: A LITERATURE STUDY - Aryana, Mahesh Khusianand; Fahmi, Muhammad; Mas’ud, Ali (PT Altin Riset Publishing, 2025)
The crisis of adolescent character in the digital era has become an increasingly complex issue along with the rapid development of technology, information globalization, and changes in social interaction patterns. Although many studies have highlighted the moral issues of the younger generation, studies that specifically examine the role of Islamic Religious Education (PAI) in integrating religious values with digital ethics are still limited. This study aims to analyze the strategic role of PAI in shaping the character of Muslim adolescents who are moral, integrity, and wise in using technology in the midst of the challenges of the digital era. This research uses a qualitative approach with a literature study design (library research) that focuses on the analysis of various scientific articles, books, and previous research results that are relevant to the themes of Islamic education, morality, and adolescent social behavior. The results of the study show that adolescent character crises are characterized by decreased spiritual awareness, weakened social empathy, increased consumptive behavior, and dependence on technology which leads to moral degradation. In this context, PAI has a fundamental role in overcoming these various symptoms through strengthening spiritual values, internalizing morals, teacher examples, and Islamic digital literacy. The implementation of technology adaptive PAI not only instills religious understanding cognitively, but also forms ethical awareness and moral responsibility in the use of digital media. This research contributes theoretically to the development of contextual and integrative Islamic education concepts, and practically provides a new direction for educational institutions to design curricula and learning strategies that are relevant to the challenges of the digital era. The conclusion of this study emphasizes that the transformation of PAI pedagogy is a necessity so that religious education not only functions as a transmission of spiritual values, but also as a means of forming digital characters based on Islamic values, so as to be able to give birth to a young generation who are religious, noble, and ethical in the virtual and real world.